Development of Ultra-Wideband (UWB)Horn Antenna Using Approximation Method - Othman, M.A.; Othman, A.R.; A.Aziz, M.Z.A.; Saysoo, N. (2012)
This paper presents a design of an ultra wide-band (UWB) horn antenna for microwave imaging radar system. The key purpose of the study is to design a horn antenna which is used in medical imaging system. The proposed antenna operates within 3.1-10.6 GHz as it is the band allocated for medical industry usage. The antenna known as a directional antenna which is supported by rectangular waveguide. The horn antenna is purposely chosen to design in order to increase the directivity of the antenna within 15-20 dB and achieve higher gain and wider bandwidth as possible. This horn antenna is capable to produce return loss as minimum as possible. The antenna is designed and simulated using CST Microwave Studio. The simulation results show that the pyramidal horn antenna structure exhibits low VSWR as well as good radiation pattern over 3.1-10.6 GHz frequency band